If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(3p + 4) + -37 = 2(2p + 5) Reorder the terms: -7(4 + 3p) + -37 = 2(2p + 5) (4 * -7 + 3p * -7) + -37 = 2(2p + 5) (-28 + -21p) + -37 = 2(2p + 5) Reorder the terms: -28 + -37 + -21p = 2(2p + 5) Combine like terms: -28 + -37 = -65 -65 + -21p = 2(2p + 5) Reorder the terms: -65 + -21p = 2(5 + 2p) -65 + -21p = (5 * 2 + 2p * 2) -65 + -21p = (10 + 4p) Solving -65 + -21p = 10 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. -65 + -21p + -4p = 10 + 4p + -4p Combine like terms: -21p + -4p = -25p -65 + -25p = 10 + 4p + -4p Combine like terms: 4p + -4p = 0 -65 + -25p = 10 + 0 -65 + -25p = 10 Add '65' to each side of the equation. -65 + 65 + -25p = 10 + 65 Combine like terms: -65 + 65 = 0 0 + -25p = 10 + 65 -25p = 10 + 65 Combine like terms: 10 + 65 = 75 -25p = 75 Divide each side by '-25'. p = -3 Simplifying p = -3
| 1+1+1+1+1*0=x | | -13-2b=b-7 | | -3p+8=5-(8p+4) | | 2-8(4y-7)= | | (2.35+2.71i)-(4.91+3.32i)=0 | | 1x+7=3x+1 | | n/5=1.6 | | 6(t-2)+8t=7(2t+4)-9 | | 7x+3y+x=16+3 | | 4+(6-7p)-2= | | 7x+1=5x-3 | | 3(x+9)=18 | | -14b+7a+2a=-5b | | x+(x+28)(2x-38)=652 | | 2y^3-13y^2+6y=0 | | x^3+x^2+2x+2=0 | | 16v^6w^7+22v^2w^6y^4= | | 7x-10=15+2x | | x-42=51 | | 3mx^2-2mx+2=x(6-5x) | | 5x-4y+9y=-15x+5 | | x+8=29 | | 0.6x+7=21 | | 8m-15m=56 | | 80z^8-45z^6=0 | | 3d-5=7d-12 | | 0.5x-4=6 | | -2t+4t-7s=9s | | 0.4x+10=20 | | 8+3(s-4t)= | | -4y-3x-x=-16y | | 3y-2x^2=x |